2007
DOI: 10.1007/s00787-007-1003-7
|View full text |Cite
|
Sign up to set email alerts
|

Tic disorders and ADHD: answers from a world-wide clinical dataset on Tourette syndrome

Abstract: Subjects with TS have high rates of ADHD and complex associations with other disorders. Clinically the findings confirm other research indicating the importance of ADHD in understanding the behavioural problems often associated with the diagnosis of TS. Additional ADHD comorbidity should be taken into account in diagnosis, management, and training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
139
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(150 citation statements)
references
References 37 publications
4
139
0
7
Order By: Relevance
“…The most disabling symptoms for the child are those of ADHD, sleeping problems (e.g., insomnia, sleepwalking and periodic leg movements) and anger control [11]. A large international study stressed that ADHD is present in approximately 55% of children afflicted with GTS and represents the main associated disorder in this segment of the general population [25]. Among adults with GTS, OCD, anxiety and depression become the most prevalent symptoms.…”
Section: ▪ Multiple Dimensions Of Gts and Concomitant Symptomsmentioning
confidence: 99%
“…The most disabling symptoms for the child are those of ADHD, sleeping problems (e.g., insomnia, sleepwalking and periodic leg movements) and anger control [11]. A large international study stressed that ADHD is present in approximately 55% of children afflicted with GTS and represents the main associated disorder in this segment of the general population [25]. Among adults with GTS, OCD, anxiety and depression become the most prevalent symptoms.…”
Section: ▪ Multiple Dimensions Of Gts and Concomitant Symptomsmentioning
confidence: 99%
“…Freeman et al, (2000) established that anger control problems, sleep difficulties, coprolalia, and self-injurious behavior, reached high levels in GTS individuals with comorbidity. Large epidemiological studies also showed that the most frequent comorbidity in GTS is ADHD in children and OCD in adults, affecting each about 50% of GTS patients (Alsobrook & Pauls, 2002;Freeman, 2007;Freeman et al, 2000). Studies are frequently compromised because of not factoring out comorbidity.…”
Section: Comorbidity and Associated Disordersmentioning
confidence: 99%
“…TS impacts approximately 1-10 in 1000 children [2][3][4] and is commonly associated with other psychiatric disorders including attention deficit hyperactivity disorder (ADHD) [5][6][7], obsessive-compulsive disorder (OCD) [6], mood disturbances [8,9], disruptive behaviors [10], and learning disorders [11]. In addition, youth with TS often experience peer victimization [12, 13•], self-concept deficits [14•], and interpersonal difficulties [15, 16•], particularly those with comorbid autism spectrum disorders (ASD) [17,18].…”
Section: Introductionmentioning
confidence: 99%